The Architecture of Strategic Decision-Making in Islamic Education: Leadership, Governance, Values, and Institutional Transformation - Yeni Tri Nur Rahmawati (Education and Sociedad Journal, 2025)
Strategic decision-making is increasingly recognized as a critical component of institutional development in Islamic education, particularly amid changing educational demands, organizational complexity, and growing expectations for effective governance. However, existing scholarship remains fragmented, with leadership, governance, Islamic values, and institutional development often examined as separate dimensions. This systematic review aims to reconstruct the architecture of strategic decision-making in Islamic education by examining how leadership capability, participatory governance, Islamic values, and institutional context interact to shape strategic choices and institutional transformation. The study employed a systematic literature review guided by the PRISMA 2020 framework, using Scopus and Web of Science as the principal databases. Relevant literature was identified through combinations of keywords related to strategic decision-making, Islamic education, educational leadership, governance, Islamic leadership, strategic management, and institutional development. The selected literature was analyzed through thematic synthesis to identify recurring concepts, relationships, and explanatory patterns. The review indicates that strategic decision-making in Islamic education is not merely a rational managerial process but a context-sensitive, participatory, and value-oriented organizational process. Leadership provides strategic judgment and sense-making, while participatory governance strengthens deliberation, stakeholder engagement, and accountability. Islamic values, particularly amanah, ‘adl, shūrā, maslahah, and mas’uliyyah, provide an ethical architecture for evaluating institutional choices. The review further shows that strategic decisions contribute to institutional transformation only when supported by strategic alignment, implementation capacity, organizational action, and organizational learning. Based on these findings, the study proposes an integrated architecture connecting institutional challenges, leadership and governance, strategic decision-making, implementation, organizational learning, and institutional transformation. The framework offers a conceptual foundation for strengthening strategic management in Islamic educational institutions.